ENGLISH PARAPHRASING TROUGH INITIAL STAGE TECHNIQUE TO DEVELOP WRITING SKILL - Nina Arfiani; Nursida Mauke; Mukmin Mukmin (BABASAL English Education Journal, 2021)
Abstract The purpose of this research is to know whether the initial stage can improve writing skill, to find out how their paraphrase capabilities result using the initial stage, and to know the students’ writing skill. This research employed quasi experimental design. Independent variable of this research was the initial stage technique and the dependent variable was the students’ writing skill. The population of this research was the eleventh grade students of MAN 1 Luwuk Banggai in 2020/2021 academic year. The way of taking the sample was by using purposive sampling. The samples were class XI IPA 1 as the experimental group and class XI IPA 2 as the control group. The test consisted of pre-test and post-test. Data were analyzed statistically. After analyzed the data, the result revealed that the t-counted was 14.38 with a degree of freedom 70 and a significance level of 0.05, t-table was 1.666. Therefore, the t-test result was higher than the t-table. It means that the hypothesis was accepted. In conclusion, the result showed that the initial stage technique of paraphrasing can develop writing skill of the eleventh grade students’ of MAN 1 Luwuk Banggai. Keywords: Develop; Writing skill; Initial Stage Technique.